The Use of Interactive Audio-Visual PPT Media to Improve Interest in Learning Arabic Language in the Material of Kalam Grade VII at Madrasah Tsanawiyah Negeri Dua Subang - Dadang Hidayatuloh; Nanang Kosim; Aditya Fitrah; Dadan Nugraha (UIN Sunan Gunung Djati Bandung, 2025)
One of the skills that needs to be strengthened in Arabic is maharoh kalam which must be learned for people who want to know Arabic. Kalam learning for students at Madrasah Negeri Dua Subang using Audio Visual media is one way for a teacher to be successful in the classroom in meeting effective learning goals. The problem is that Madrasah Negeri Dua Subang has not implemented it. Therefore, the aim of this research is to determine the increase in students' interest in learning Arabic using Interactive Audio Visual PowerPoint PPT media. This research was carried out in several cycles with a qualitative approach by collecting data by means of observation, interviews and documentation studies. The data analysis carried out was using data reduction methods, presenting data and drawing conclusions. The results of learning research at Madrasah Negeri Dua Subang using Interactive Audio Visual PowerPoint PPT media are that students can increase their interest and more easily learn Arabic to the next level. his study aims to evaluate the effectiveness of using audiovisual media in the form of interactive PowerPoint (PPT) presentations in increasing the learning interest of Class VII students at Madrasah Tsanawiyah Negeri 2 Subang. The research method used is descriptive quantitative, with data collected through observations, interviews, and questionnaires with teachers and students. The results of the study show that the use of interactive PPTs significantly increases students' interest in learning. This media can capture students' attention, make learning more engaging, and facilitate more active interaction between teachers and students. Teachers reported an increase in students' enthusiasm and motivation to participate in lessons. Overall, the use of interactive audiovisual PPT media has proven to be effective in increasing the learning interest of Class VII students at Madrasah Tsanawiyah Negeri 2 Subang.